Direct Synthesis of Nanosheet‐Stacked Hierarchical "Honey Stick‐like" MFI Zeolites by an Aromatic Heterocyclic Dual‐Functional Organic Structure‐Directing Agent. Issue 34 (27th May 2021) - Wang, Risheng; Peng, Zhihua; Wu, Pingping; Lu, Jinzhi; Rood, Mark J.; Sun, Hongman; Zeng, Jingbin; Wang, Youhe; Yan, Zifeng
Abstract: Soft template designing is the most promising strategy for the synthesis of zeolite nanosheets. MFI nanosheets directed by soft templates (containing long‐chain alkyl groups or aromatic groups as hydrophobic component) can be found frequently; however, so far, MFI nanosheets synthesized by soft templates with aromatic heterocycle groups (e. g., s ‐triazine groups) are rare. Herein, a nanosheet‐stacked hierarchical MFI zeolite (NSHM) has been synthesized by using a triply branched s ‐triazine‐based surfactant as a bifunctional organic structure‐directing agent. On the basis of a geometrical match relationship, a formation model has been proposed. Synthesized NSHM had abundant mesopores stacked by nanosheets and exhibited a high surface area (430 m 2 ⋅ g −1 ). The 1 wt% Pd/NSHM attained a significant increase in yield of cyclohexanol/cyclohexanone mixture (from 66 to 85 %) in the oxidation of cyclohexane compared with Silicalite‐1 and SBA‐15 as supports. Abstract : Between the sheets : A nanosheet‐stacked hierarchical MFI zeolite (NSHM) has been synthesized by using a triply branched s ‐triazine‐based surfactant as a bifunctional soft template, and a mechanism for its formation is proposed. The NSHM had abundant mesopores created by the stacked nanosheets and a high surface area (430 m 2 ⋅ g −1 ). Moreover, superior catalytic performance in the oxidation of cyclohexane is shown by NSHM with palladium loading.